Analisis Faktor Perilaku Ekonomi dan Sosial terhadap Minat Investasi Saham pada Mahasiswa - Ni Kadek Gita Dwipayani Surya; I Putu Hedi Sasrawan (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Stocks are one of the most widely preferred capital market instruments among both novice and experienced investors. Generation Z, particularly university students, constitutes the majority of investors in Indonesia, supported by the presence of Investment Galleries. However, at the Faculty of Economics and Business, Universitas Udayana, students’ interest in investing remains relatively low, resulting in a gap between the potential and the actual realization of students’ investment interest. This study aims to analyze the effect of investment knowledge, social environment, income, and gender on stock investment interest among undergraduate students from the 2022 to 2025 cohorts. The research was conducted at the Faculty of Economics and Business, Universitas Udayana. This study employs a quantitative approach with an associative research design, involving a sample of 97 respondents. The analytical technique used is logistic regression, including goodness-of-fit tests, pseudo R-square, omnibus test, and Wald test. The results indicate that all independent variables simultaneously have a significant effect on the dependent variable. Partially, investment knowledge, social environment, and gender have a positive and significant effect on stock investment interest, where male students demonstrate a higher level of interest compared to female students. Meanwhile, income does not have a significant effect on students’ stock investment interest.